Melatonin Minimizes the Impact of Oxidative Stress Induced by Hydrogen Peroxide in Saccharomyces and Non-conventional Yeast - Vázquez, Jennifer; Grillitsch, Karlheinz; Daum, Günther; Mas, Albert; Torija, María-Jesús; Beltran, Gemma (Frontiers in Microbiology, 2018)
Melatonin (N-acetyl-5-methoxytryptamina) is synthesized from tryptophan by Saccharomyces cerevisiae and non-conventional yeast species. Antioxidant properties have been suggested as a possible role of melatonin in a Saccharomyces cerevisiae wine strain. However, the possible antioxidant melatonin effect on non-Saccharomyces species and other strains of S. cerevisiae must be evaluated. The aim of this study was to determine the antioxidant capacity of melatonin in eight S. cerevisiae strains and four non-conventional yeasts (Torulaspora delbrueckii, Metschnikowia pulcherrima, Starmerella bacillaris and Hanseniaspora uvarum). Therefore, the ROS formation, lipid peroxidation, catalase activity, fatty acid composition and peroxisome proliferation were investigated. The results showed that the presence of melatonin increases peroxisome accumulation and slightly increases the catalase activity. When cells grown in the presence of melatonin were exposed to oxidative stress induced by H2O2, lower ROS accumulation and lipid peroxidation were observed in all tested strains. Therefore, the increased catalase activity that was a consequence of oxidative stress was lower in the presence of melatonin. Moreover, the presence of MEL modulates cell FA composition, increasing oleic and palmitoleic acids and leading to higher UFA/SFA ratios, which have been previously related to a higher tolerance to H2O2. These findings demonstrate that melatonin can act as an antioxidant compound in both S. cerevisiae and non-Saccharomyces yeasts.